Management from a multidisciplinary perspective of phlebitis related to peripheral venous catheter insertion: An international Delphi study - Alba Torné‐Ruiz; Montse Sanromà‐Ortiz; Alex Corral‐Nuñez; Daniel Medel; Judith Roca; Judith García‐Expósito (Wiley, 2024)
Abstract Aim To determine the consensus and importance of care practices related to the management of peripheral venous catheter (PVC)‐related phlebitis in hospitalized patients through the views of experts from different disciplines. Background PVCs are commonly used in hospitals but are associated with complications such as phlebitis. Their management differs widely, and studies are heterogeneous. Design Delphi method. Methods Four stages: problem area (with Web of Science bibliometric review in July 2022), panel members, two Delphi rounds and closing criteria. In the Delphi survey, experts answered an online questionnaire based on assessment, treatment and follow‐up dimensions (September 2022-February 2023). Statistical analyses were conducted of frequencies, percentages, measures of central tendency and levels of dispersion (QD). A space for comments was created, and a thematic analysis conducted of them. Results Eighteen experts (nurses, doctors and pharmacists) participated in the Delphi rounds. Forty‐five activities were identified: 19 in assessment, 15 in treatment and 11 in follow‐up. A high consensus level (QD ≤ 0.6) was found in five activities (11.12%), moderate level (0.6 < QD < 1.0) in 19 (42.22%) and low level (QD > 1.0) in 21 (46.66%). Seven themes were determined (patient perspective, lack of consensus, low evidence‐based practices, stage‐based treatments, prevention activities, high variability in practice and specialist teams and interdisciplinary work). Conclusion The importance of systematic assessment scales is highlighted together with consensus on signs and symptoms (pain, redness, inflammation, palpable cord and induration). Treatment according to severity and daily visual recording and monitoring are emphasized along with the need for patient participation and healthcare literacy. A high level of consensus was obtained in 11% of the activities, showing the large variability of criteria and interventions for phlebitis management. Highlighted needs include working in a team, the use of specialist teams and promoting evidence‐ and prevention‐based activities. Relevance to Clinical Practice Clinical variability is noted and, therefore, the importance of consensus on standardized care for PVC phlebitis and evidence‐based practice. Reporting Method Delphi studies (CREDES). Patient or Public Contribution Experts contribution.